Henry Ford : A 4D BOOK - Simons, Lisa M. Bolt, 1969-; Shores, Erika L.; Server, Jessica; Whitman, Charmaine (North Mankato, Minnesota : CAPSTONE PRESS, 2018)
"Henry Ford wasn't just an inventor. He was also a smart businessman. Young readers will discover how this famous maker of the Model T and the moving assembly line helped change the world. Download the Capstone 4D app to access a variety of bonus content"-- Publisher.
Includes index.
Bibliography : page 23
Interest age level: Ages 6-9.
Keywords: Ford, Henry, -- Juvenile literature -- 1863-1947; Automobile industry and trade -- Juvenile literature -- Biography -- United States; Industrialists -- Juvenile literature -- Biography -- United States